Herpes Simplex Pneumonia in an Immunocompetent Patient With Progression to Organizing Pneumonia - Brooke Mills BS; Atul Ratra MS, MBA; Amal El-Bakush MD; Shrinivas Kambali MD; Kenneth Nugent MD (SAGE Publishing, 2014)
Background . Organizing pneumonia is an uncommon diffuse interstitial lung disease that affects the terminal and respiratory bronchioles, alveolar ducts, and alveoli. Most cases are idiopathic, but some are associated with infections. We present an uncommon case of organizing pneumonia associated with herpes simplex virus-1 (HSV-1). Case . A 39-year-old man with hypertension presented with dyspnea, fever, and productive cough for 2 weeks. He was treated for 5 days for acute bronchitis as an outpatient with no improvement. His examination revealed mild respiratory distress, O 2 saturation 92% on room air, and right sided crackles. Labs included a white blood cell count of 19 300/µL. His chest x-ray showed bilateral infiltrates greater on the right. Bronchoalveolar lavage was positive for HSV-1; transbronchial biopsies showed focal pneumonitis with plentiful intra-alveolar macrophages. His respiratory status progressively deteriorated, and he was intubated for mechanical ventilation. He received 10 days of intravenous (IV) antibiotics and 14 days of IV acyclovir. He was readmitted 10 days later with worsening symptoms and was intubated for respiratory failure. His CT chest showed diffuse, patchy consolidation of both lungs, right more than left. Open lung biopsy showed extensive organizing pneumonia, diffuse alveolar damage, intra-alveolar macrophages, and pleural fibrosis; he was treated with IV corticosteroids. He was extubated after 10 days; within 2 weeks his chest x-ray was markedly improved. Discussion . Organizing pneumonia is usually idiopathic; infection is one of the secondary causes. To our knowledge this is only the second reported case associated with HSV. This association may have important pathogenic and therapeutic implications.